2022
DOI: 10.51253/pafmj.v72isuppl-2.2977
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Iron Deficiency Anemia in Young Females with Migraine

Abstract: Objective: To determine the frequency of iron deficiency anaemia among young female migraine patients and look for the factors related to the presence of anaemia. Study Design: Cross-sectional study. Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Feb 2019. Methodology: One hundred and thirty young female patients with migraine presenting at our hospital were enrolled in this study. Diagnosis of Migraine was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…A risk factors of IDA include food intake pattern, female gender, parasites, low teaching level, low income, female aging (46) and menstruation (causes headache) (47). This study agrees with Rashid et al, (2022) who note that IDA was a common problem in migraine young females (48). Lee, et al, (2021) found increase of migraine risk in IDA patients (49).…”
Section: Discussionsupporting
confidence: 91%
“…A risk factors of IDA include food intake pattern, female gender, parasites, low teaching level, low income, female aging (46) and menstruation (causes headache) (47). This study agrees with Rashid et al, (2022) who note that IDA was a common problem in migraine young females (48). Lee, et al, (2021) found increase of migraine risk in IDA patients (49).…”
Section: Discussionsupporting
confidence: 91%
“…Iron accumulation in the brain, particularly in regions associated with migraine pathophysiology, and dietary iron's effects on migraine in women of different ages have been noted in other studies (17)(18). A related study conducted at the same hospital in 2018 focusing on female migraine patients found a significant correlation between menstrual abnormalities and IDA in adolescent patients, reinforcing the prevalence of IDA among migraine patients in Pakistan (19)(20).…”
Section: Discussionmentioning
confidence: 59%